Evaluation of Microchip-Based Point-Of-Care Device “Gazelle” for Diagnosis of Sickle Cell Disease in India - Shrivas, Shweta; Patel, Madhav; Kumar, Rajat; Gwal, Anil; Uikey, Ramswaroop; Tiwari, Shashi Kant; Verma, Anil Kumar; Thota, Priyaleela; Das, Aparup; Bharti, Praveen Kumar; Shanmugam, Rajasubramaniam (Frontiers in Medicine, 2021)
Sickle cell disease is a major public health problem in India. Lack of rapid and reliable diagnostic methods result in many avoidable deaths in affected population. Current diagnostic tools are laboratory based, expensive and need trained manpower. Here, we evaluated the performance of a microchip-based cellulose acetate electrophoresis test, “Gazelle” in the tribal-dominated Indian states of Chhattisgarh and Madhya Pradesh. A total of 1,050 patients were screened by sickle cell solubility, hemoglobin (cellulose acetate) electrophoresis, high-performance liquid chromatography (HPLC) and Gazelle. Of the total 1,027 test results obtained, 960 tests were “Valid” (93.5%) and included in the analysis. Gazelle identified all patients with disease (HbSS and Thalassemia Major) with 100% accuracy. Gazelle demonstrated 100% sensitivity when comparing sickle cell disease (SCD) vs. sickle cell trait and SCD vs. normal. Specificity was 98.9% and 99.5% when comparing SCD vs. trait and trait vs. normal, respectively. Specificity was 99.8% when comparing SCD vs. normal and sensitivity was 99.3% when comparing trait vs. normal. Overall, Gazelle yielded a high accuracy (99.0%) compared to reference standard tests (hemoglobin electrophoresis and HPLC). Gazelle is a low-cost, rapid diagnostic test with high accuracy for detecting SCD both quantitatively and qualitatively. Gazelle can be a potential screening tool for the rapid diagnosis in resource limited settings and developing countries with high burden of hemoglobin disorders.